Нижненемецкий язык Германии: статус и современное состояние - Герасімова, Є.М.; Перепечкіна, С.Є. (Культура народов Причерноморья, 2013)
В связи с развитием новой северо-немецкой формы разговорной речи возникает
необходимость идентификации и описания региональных и локальных особенностей языка в аспекте их
территориальной, социальной и ситуативной обусловленности. Проведенное исследование с
применением социолингвистических методов имело целью выяснить, как часто и какие именно
лексические единицы нижненемецких диалектов используются и насколько они еще «узнаваемы».
Ключевые слова: нижненемецкие диалекты, статус, социолингвистическое исследование У зв’язку з розвитком у північній Німеччині нової форми розмовної мови виникає необхідність
ідентифікації та опису регіональних та локальних особливостей мовлення в аспекті їх територіальної,
соціальної і ситуативної зумовленості. Проведене дослідження з використанням соціолінгвістичних
методів мало метою вияснити, як часто і яки лексичні одиниці нижньонімецьких діалектів
використовуються і наскільки вони ще можуть бути ідентифіковані мовцями.
Ключові слова: нижньонімецькі діалекті, статус, соціолінгвістичне дослідження. This article examines the status and functional aspect of Low German used in Northern Germany.
During the last three decades a new spoken language variety has become widespread in this area. It is regarded
as a contact variety, specifically a type of standard German with the original Low German dialect substratum.
The documentation, description and analysis of dialectal variation in Northern Germany in terms of regional,
social and situational usage are the primary purpose of the SiN project (Sprachvariation in Norddeutschland).
Documenting object language data along with the speakers' subjective opinions and reflexions on language
norm will allow for compiling the first ever text corpus of Low German substandard dialect.
The purpose of our sociolinguistic research was to determine whether certain Low German lexical entities were
still in use and whether their meaning could be correctly deciphered. This article is based on a study of 35
individuals aged 23-65 coming predominantly from Hamburg. During the survey, the respondents were
presented with a number of common nouns, verbs and adjectives (25 for every part of speech) selected from
dialect dictionaries (Plattmakers-Wörterbuch and Plattdeutsches Wörterbuch). The survey revealed that some of
these words (tüdelig, baff, snaken, lütt, Deern, Huus, Vadder, gackern etc) were indeed largely used by those
surveyed. Some words did not seem familiar to any of them (lurig, blied, smööd, drook, schöveln, warrn,
Herrgottskoh). In many cases the participants misidentified the meaning of Low German words, which they
confused with similar-sounding or similarly spelled High German or English words: warrn (werden) was taken
to mean warnen; hebben (haben) was interpreted as heben; natt (naß) as nett; Huut (Haut) as Hut; butt (grob)
as aber (cf. English but); fuul (faul) as voll (cf. English full).
Low German in its pure form is rarely spoken today. It has been gradually supplanted by Missingsch, a contact
variety of Low and High German that may warrant further research.
Keywords: Low German dialects, variety status, sociolinguistic research